An experimental investigation of the stress-strain distribution in high strength concrete deep beams - Mohammad, M.; Jumaat, Mohd Zamin; Chemrouk, M.; Ghasemi, A.; Hakim, S.J.S.; Najmeh, R. (2011)
This paper discusses the behaviour, design and analysis of high strength reinforced concrete (HSC) deep beams regarding the neutral axis variation. The study of this structural element is motivated by the lack of a clear procedure for the design of these structural elements, which have many useful applications such as in foundations, in offshore structures, in tall buildings and in bridges. It should be noted however, that the design of these structural elements is not covered sufficiently by the existing codes of practices. For example, the British code BS8110 explicitly states that, for design of deep beams, reference should be made to specialist literature. Other codes such as the ACI, the draft Euro code EC/2, the Canadian code and the CIRIA guide No.2b present some design guidelines based on empirical analysis. The present research consists of six HSC deep beams designed and casted with self compacted concrete (SCC). The main goal of this research is to study the stress-strain distribution along the beam section at mid-span and discuss the variation of the neutral axis within the depth. Sufficient horizontal and vertical web reinforcement are used to ensure tensile reinforcement yielding before shear failure. It was decided to keep the beam's length, depth and thickness constant while varying the tensile reinforcement percentage. Strain gauges have been attached on the concrete surface, on the tensile reinforcement and on the horizontal and vertical web bars to monitor the strains, both in concrete and in the different reinforcement bars. The data show clearly that the distribution of strains, and hence of stresses, in the deep beams studied is completely different from the linear one, commonly accepted for ordinary.